Examining Social Media Marketing Strategies for Building Brand Awareness: A Case Study of Instagram Foom.id - Muhammad Flavio Hafizh Putra Kuntjoro; Silvanus Alvin (PT FORMOSA CENDEKIA GLOBAL, 2023)
The rapid development of technology in the digital era has facilitated easy and quick communication. This has led to the emergence of digital marketing innovations that significantly impact the sales of products and services. In the electronic cigarettes industry, Foom_id has been actively engaging in marketing communication through social media since 2019. The objective of this research is to examine the social media marketing strategies implemented by Foom_id on Instagram to enhance brand awareness. This qualitative research adopts a case study methodology. Data collection involves in-depth interviews with individuals responsible for managing Foom_id's Instagram account. Construct validity is employed to ensure data validity, while data analysis utilizes the technique of pattern matching. The findings of this study indicate that the utilization of social media marketing strategies in marketing communication through Instagram can effectively enhance brand awareness. Foom_id creates engaging content, including Q&A sessions, collaborations, and trending topics, to increase consumer awareness